1995
DOI: 10.1530/eje.0.1330277
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid and plasma levels of parathyroid hormone-related protein and hormonal modulation of its secretion by amniotic fluid cells

Abstract: Parathyroid hormone-related (PTHrP), the major mediator of humoral hypercalcemia of malignancy, may also regulate placental calcium flux, uterine contraction and fetal tissue development. In the present study, we demonstrated that the mean immunoreactive PTHrP concentrations in amniotic fluid at mid-gestation (21.2 +/- 3.7 pmol/l) and at term (19.0 +/- 2.7 pmol/l) were 13-16-fold higher than levels measured in either fetal (1.6 +/- 0.1 pmol/l) or maternal plasma (1.4 +/- 0.3 pmol/l) at term and equal to levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The findings of the present report are consistent with those of Papantoniou et al (1996), who reported low but detectable levels of PTHrP(1-86) that were not different from maternal values. Amniotic fluid PTHrP concentrations from term human pregnancy were found to be approximately 40 pmol/l, which is consistent with other reported values (Dvir et al 1995, Wlodek et al 1995. As there is no detectable PTHrP in fetal urine (Ferguson et al 1992, Wlodek et al 1995, it has been suggested that the PTHrP found in amniotic fluid is derived from the amnion.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the present report are consistent with those of Papantoniou et al (1996), who reported low but detectable levels of PTHrP(1-86) that were not different from maternal values. Amniotic fluid PTHrP concentrations from term human pregnancy were found to be approximately 40 pmol/l, which is consistent with other reported values (Dvir et al 1995, Wlodek et al 1995. As there is no detectable PTHrP in fetal urine (Ferguson et al 1992, Wlodek et al 1995, it has been suggested that the PTHrP found in amniotic fluid is derived from the amnion.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis should be clarified both in vitro and in clinical studies. (Inoue et al, 1993;Endo et al, 1994;Dvir et al, 1995). In addition, a progestin, medroxyprogesterone acetate, dose-dependently inhibited PTHrP secretion from the PgR-positive KPL-3C cell line in our previous study (Kurebayashi et al, 1996).…”
Section: Reproducibility Of the Experimental Resultsmentioning
confidence: 80%
“…Regulation of PTHrP secretion has been widely studied in cancer cell lines (Deftos et al, 1989;Emly et al, 1994;Endo et al, 1994;Merryman et al, 1994;Rizzoli et al, 1994), human T-cell lymphotrophic virus, type I-infected T cells (Inoue et al, 1993), normal and transformed keratinocytes Kremer et al, 1991;Allinson and Drucker, 1992), primary cultures of mammary epithelial cells (Thiede, 1989;Ferrari et al, 1992;Sebag et al, 1994), pituitary cells (Holt et al, 1994) and cultured amniotic fluid cells (Dvir et al, 1995). Steroid hormones, such as glucocorticoids, vitamin D and its analogues and progestins are reported to inhibit PTHrP secretion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the level of PTHrP was undetectable in the early postpartum, the placenta was probably the major source of secretion. However, considering the improvement of the woman' arthralgia only after the removal of the fibroma and knowing that secretion of PTHrP by the fibroma could be enhanced by estrogens and by human placental lactogen14, 15, 40, it is reasonable to think that the fibroma played an active part in the hypercalcemia. We therefore hope that following removal of the fibroma, the risk of recurrence of hypercalcemia in future pregnancies will be low.…”
Section: Case Outcomes – Perspectivesmentioning
confidence: 99%